2016
DOI: 10.1051/0004-6361/201628925
|View full text |Cite
|
Sign up to set email alerts
|

High-redshift supernova rates measured with the gravitational telescope A 1689

Abstract: Aims. We present a ground-based, near-infrared search for lensed supernovae behind the massive cluster Abell 1689 at z = 0.18, which is one of the most powerful gravitational telescopes that nature provides. Methods. Our survey was based on multi-epoch J-band observations with the HAWK-I instrument on VLT, with supporting optical data from the Nordic Optical Telescope. Results. Our search resulted in the discovery of five photometrically classified, core-collapse supernovae with high redshifts of 0.671 < z < 1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 99 publications
0
39
1
Order By: Relevance
“…The rate of CC SNe at the relevantẑ ∼ 2 is R CC (ẑ) ∼ 3 × 10 5 Gpc −3 yr −1 (Strolger et al 2015; see also Dahlen et al 2004;Graur et al 2011;Melinder et al 2012;Dahlen et al 2012;Cappellaro et al 2015;Petrushevska et al 2016). The fraction of CC SNe that belong to the Ib/c class is found to be f Ibc ∼ 0.4 at a mean redshift z ∼ 0.25 by Cappellaro et al (2015); combining with local estimates (e.g.…”
Section: Central Engine Activity Time Distribution P E (T E )mentioning
confidence: 54%
“…The rate of CC SNe at the relevantẑ ∼ 2 is R CC (ẑ) ∼ 3 × 10 5 Gpc −3 yr −1 (Strolger et al 2015; see also Dahlen et al 2004;Graur et al 2011;Melinder et al 2012;Dahlen et al 2012;Cappellaro et al 2015;Petrushevska et al 2016). The fraction of CC SNe that belong to the Ib/c class is found to be f Ibc ∼ 0.4 at a mean redshift z ∼ 0.25 by Cappellaro et al (2015); combining with local estimates (e.g.…”
Section: Central Engine Activity Time Distribution P E (T E )mentioning
confidence: 54%
“…For observed SN Ia rates we use the data compilation of Melinder et al (2012) and supplement this with rates more recently reported by Okumura et al (2014), Cappellaro et al (2015, Rodney et al (2014) and Graur et al (2014). For CCSNe we again use the compilation of Melinder et al (2012) and additionally show the rates reported by Taylor et al (2014), Strolger et al (2015) and Petrushevska et al (2016).…”
Section: Observational Constraintsmentioning
confidence: 99%
“…The results are shown is Table 2 together with the previous estimates for A1689 and A370 from P18 for comparison. For more details regarding the estimates presented in this section, we refer to our previous work (Petrushevska et al 2018(Petrushevska et al , 2016Goobar et al 2009).…”
Section: Prospects For Observing Lensed Supernovae Behind the Hff Galmentioning
confidence: 99%
“…The magnification boost provided by the cluster lenses enhances the possibility of observing SNe at unprecedented distances, which enables to study their properties and their possible evolution with redshift that otherwise would be undetectable . Furthermore, discoveries of high redshift SNe can be used to pinpoint the SN rates at very high redshifts (z > 2) where they are poorly measured (Sullivan et al 2000;Gunnarsson and Goobar 2003;Petrushevska et al 2016).…”
Section: Introductionmentioning
confidence: 99%